2019
DOI: 10.31234/osf.io/fx5bq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loneliness and the Big Five Personality Traits: A Meta-Analysis

Abstract: This preregistered meta‐analysis (k = 113, total n = 93 668) addressed how the Big Five dimensions of personality (extraversion, agreeableness, conscientiousness, neuroticism, and openness) are related to loneliness. Robust variance estimation accounting for the dependency of effect sizes was used to compute meta‐analytic bivariate correlations between loneliness and personality. Extraversion (r = −.370), agreeableness (r = −.243), conscientiousness (r = −.202), and openness (r = −.107) were negatively related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…These findings might indicate that neuroticism reflects the overall propensity of individuals to experience negative affect, whereas loneliness reflects the tendency to experience negative affect particularly in social situations. These differences are also mirrored in moderate meta-analytic phenotypic correlations between loneliness and neuroticism in the magnitude of r=.30 (Buecker et al, 2018). Thus, despite their common core, several mechanisms seem to pull the development of loneliness and neuroticism in different directions in the long run (Spithoven et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These findings might indicate that neuroticism reflects the overall propensity of individuals to experience negative affect, whereas loneliness reflects the tendency to experience negative affect particularly in social situations. These differences are also mirrored in moderate meta-analytic phenotypic correlations between loneliness and neuroticism in the magnitude of r=.30 (Buecker et al, 2018). Thus, despite their common core, several mechanisms seem to pull the development of loneliness and neuroticism in different directions in the long run (Spithoven et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, the results of several studies support the subjective nature of loneliness by showing that the association between the objective size of individuals’ social networks and loneliness is weak, whereas aspects of relationship quality are more closely related to loneliness (Green, Richardson, Lago, & Schatten-Jones, 2001; Luhmann & Hawkley, 2016; Pinquart & Sörensen, 2001b; Stokes, 1985). A large body of research has been devoted to identifying the predictors, correlates, and consequences of loneliness (Bosma, Jansen, Schefman, Hajema, & Feron, 2015; Goossens et al, 2015; Hawkley, Masi, Berry, & Cacioppo, 2006; Hawkley, Thisted, Masi, & Cacioppo, 2010; Kamiya, Doyle, Henretta, & Timonen, 2014; Luhmann & Hawkley, 2016; Savikko, Routasalo, Tilvis, Strandberg, & Pitkälä, 2005; Shankar et al, 2011; for reviews, see Buecker, Maes, Denissen, & Luhmann, 2018; Cacioppo, Cacioppo, Capitanio, & Cole, 2015; Ernst & Cacioppo, 1999; Hawkley & Cacioppo, 2010; Hawkley & Capitanio, 2015; Pinquart & Sörensen, 2001a, 2001b). In sharp contrast, surprisingly little is known about the stability and change of loneliness across the life span.…”
mentioning
confidence: 99%
“…These traits are also associated with worse clinical profiles (Goodwin & Friedman, 2006) that are harmful to cognitive function (Song et al, 2020). Higher neuroticism and lower conscientiousness are further associated with poor social health, including greater loneliness and social isolation (Buecker et al, 2020), which can be detrimental to cognitive health (Luchetti et al, 2020;.…”
Section: Discussionmentioning
confidence: 99%
“…And indeed, openness has been identified as an investment trait (von Stumm & Ackerman, 2013), and it is consistently associated with better cognition (Sharp et al, 2010;Sutin, Stephan, Luchetti, et al, 2019). Although agreeableness may be associated with better cognitive function through its prosocial tendencies that support greater social engagement (Buecker et al, 2020) that are protective of cognition , findings reported in the literature tend to be mixed for this trait (Curtis et al, 2015;Sutin, Stephan, Damian, et al, 2019). Finally, conscientiousness, like openness, may support greater investment (Hill & Jackson, 2016) that contributes to better cognition.…”
mentioning
confidence: 99%
“…In einigen Fällen kann Einsamkeit im Zusammenhang mit Lebensereignissen, insbesondere Verlusterfahrungen auftreten 10 , 11 . Einige Studien haben zudem Zusammenhänge mit demographischen Merkmalen wie einem geringen sozioökonomischen Status 2 , 12 sowie mit individuellen Persönlichkeitsmerkmalen 13 zeigen können.…”
Section: Einsamkeitunclassified